The Efficacy and Safety of Celecoxib for Pain Management After Total Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Geng, Xiaoyuan; Zhou, Shangyou; Zhang, Xiaoyan; Liu, Xi; Cheng, Xu; Jiang, Lihua; Zhang, Donghang (Frontiers in Surgery, 2022)
Background: This study aimed to determine the efficacy and safety of celecoxib for pain management after total knee arthroplasty (TKA). Methods: PubMed, EMBASE, Web of Science and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched to identify eligible randomized controlled trials (RCTs) that compared celecoxib with a placebo in term of pain control efficacy after TKA. Primary outcomes included pain scores at 24 h, 48 h and 72 h after TKA. Secondary outcomes included the active range of motion (ROM) at 24 h, 48 h ,72 h and 7 days postoperatively, morphine consumption over 72 h after TKA, incidence of postoperative nausea and vomiting (PONV), and total blood loss after surgery. Data analysis was conducted using RevMan version 5.3. Results: Five RCTs involving 593 participants were included in the study. Compared with a placebo, celecoxib significantly reduced visual analog scale (VAS) scores at rest at 24 h (mean difference [MD] = -0.72; 95% confidence interval [CI], -1.27 to -0.17; I2 = 82%; P = 0.01), 48 h (MD = -1.51; 95% CI, -2.07 to -0.95; I2 = 0%; P < 0.00001), and 72 h (MD = -1.30; 95% CI, -2.07 to -0.54; I2 = 82%; P = 0.0009) after TKA, decreased morphine consumption over postoperative 72 h (MD = -0.73; 95% CI, -0.96 to -0.51; I2 = 96%; P < 0.00001), and increased active ROM at 48 h (MD = 13.23; 95% CI, 7.79 to 18.67; I2 = 0%; P < 0.00001), 72 h (MD = 6.52; 95% CI, 4.95 to 8.10; I2 = 68%; P < 0.00001), and 7 days (MD = 7.98; 95% CI, 3.64 to 12.31; I2 = 68%; P = 0.0003) after the operation. No significant difference was found in the active ROM at 24 h (MD = 7.60; 95% CI, -6.14 to 21.34; I2 = 94%; P = 0.28) and the incidence of PONV after surgery (risk ratio [RR] = 0.66; 95% CI, 0.40 to 1.09; I2 = 0%; P = 0.11). Conclusion: The administration of celecoxib is an effective and safe strategy for postoperative analgesia after TKA.